Empowering young minds: Transforming social studies education to foster digital ethics in elementary schools - Marsini, Marsini (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The rapid development of digital technology demands integrating digital ethics skills into the education process, including at the elementary school level. The study explores the transformation of social science teaching in elementary schools to build students' digital ethics skills. This study uses a qualitative method as a literature study, including analysing various relevant academic sources, such as journal articles, books, and previous research reports. The focus lies on how the pedagogical approach in Social Sciences can be adjusted to instil digital ethics values, such as responsible use of technology, privacy awareness, and critical thinking skills towards digital information. The study results indicate that teaching social Sciences has excellent potential as an effective medium for introducing the concept of digital ethics to students. Students can better understand the importance of ethical behaviour in the online environment through project-based learning methods, group discussions, and case studies related to social issues in the digital world. In addition, the role of teachers as facilitators is vital in guiding students to develop a critical understanding of the information they encounter online. The transformation of social science teaching integrated with digital ethics improves students' technological literacy and forms character as responsible technology users. The study's implications are expected to be a reference for educators in designing a curriculum relevant to the needs of the digital era.